2018
DOI: 10.1134/s1063772918120272
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Strongly Lensed Supernovae Behind Hubble Frontier Fields Galaxy Clusters with the James Webb Space Telescope

Abstract: Measuring time delays from strongly lensed supernovae (SNe) is emerging as a novel and independent tool for estimating the Hubble constant (H 0 ). This is very important given the recent discord in the value of H 0 from two methods that probe different distance ranges. The success of this technique will rely of our ability to discover strongly lensed SNe with measurable time delays. Here, we present the magnifications and the time delays for the multiply-imaged galaxies behind the Hubble Frontier Fields (HFF) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The Young et al (2008) prescription implies a lower limit on the rate of core-collapse (cc) SNe 1-3 SNe yr −1 . This value is consistent with results of Petrushevska et al (2018), who summed ccSNe over the six Hubble Frontier Fields (Lotz et al 2017). They found that for a JWST/NIRCam imaging cadence of four 1 hr visits per year, the rate integrated over all six HFFs is expected to be ∼0.9 ccSNe and ∼0.06 SNe Ia.…”
Section: Compact Galaxy Groups and Associationssupporting
confidence: 89%
“…The Young et al (2008) prescription implies a lower limit on the rate of core-collapse (cc) SNe 1-3 SNe yr −1 . This value is consistent with results of Petrushevska et al (2018), who summed ccSNe over the six Hubble Frontier Fields (Lotz et al 2017). They found that for a JWST/NIRCam imaging cadence of four 1 hr visits per year, the rate integrated over all six HFFs is expected to be ∼0.9 ccSNe and ∼0.06 SNe Ia.…”
Section: Compact Galaxy Groups and Associationssupporting
confidence: 89%
“…Therefore, we can constrain the supernova rate at very high redshifts by observations of strongly lensed supernovae at such high redshifts [138,315,316]. The search of lensed high-redshift supernovae can be conducted efficiently by monitoring massive clusters of galaxies [317][318][319][320][321][322].…”
Section: The Nature Of Explosive Transientsmentioning
confidence: 99%
“…The most viable observational approach is to monitor a great number of suspected galaxy-galaxy lenses using near-future observatories, e.g. the James Webb Space Telescope (JWST, Petrushevska et al 2018), the Vera Rubin Observatory (Liao 2018;Tu et al 2019), andZwicky Transient Survey (ZTF, Shu et al 2018;Goldstein et al 2019).…”
Section: Discussionmentioning
confidence: 99%